Light-activated cAMP signaling controls sodium-driven motility in Vibrio cholerae - Jun Xu; Shuichi Nakamura; Suzuna Tomoyose; Reika Shimabuku; Rintaro Tomioka; Tetsu Yamashiro (Proceedings of the National Academy of Sciences, 2026)
Light is one of the most pervasive physical cues in aquatic environments, yet its impact on nonphototrophic pathogens remains largely unexplored. Here, we show that a strain of cholera bacterium Vibrio cholerae directly couples illumination to motility through cyclic AMP (cAMP) signaling. Exposure to visible light rapidly elevates intracellular cAMP and increases swimming speed, whereas deletion of the single adenylyl cyclase gene ( cyaA ) abolishes both responses; complementation or addition of exogenous cAMP restores the phenotype. Heterologous expression of V. cholerae CyaA in an Escherichia coli Δ cyaA Δ cpdA background reconstitutes light-activated cAMP synthesis, indicating that CyaA confers photoreactivity. Purified CyaA exhibits a reversible light-dependent spectral shift consistent with flavin-dependent photochemistry, identifying it as a light-responsive cyclase. Illumination triggers rapid membrane hyperpolarization and sodium efflux, strengthening the sodium-motive force that powers the flagellar motor. This response persists under nutrient-limited conditions. Together, these findings define a light → cAMP → sodium-motive force coupling axis in V. cholerae , suggesting that ambient light may influence motility and dispersal in sunlit environments.